Virtual Team and Trust Relationship: Focus Group Interviews in Multimedia Super Corridor Status Companies - Aripin, Norizah; Mustafa, Hasrina; Hussein, Adnan (Journal of Techno-Social, 2011)
This paper aims to discuss the trust relationship in virtual teams in Multimedia Super Corridor (MSC) status companies. The study used qualitative method that is phenomenology approach through focus group interviews. In-depth interview were also used with semi-structured and openended questions. The interviews involved six staffs at different position in virtual team (two team leaders, and four team members). The interviews were recorded, transcribed and analyzed according to the thematic analysis. Results showed that dimensions on virtual team trust relationship including interpersonal communication, personality, team members size, face-to-face meeting needs, safety information when discussing face-to-face in public places, and difficulty to recall interaction via video conferencing with other team members.